NEGLIGENCE CRIMINAL ACT THAT CAUSES TRAFFIC ACCIDENTS AND RESULTS IN SERIOUS INJURY AND DEATH OF OTHER PEOPLE - Yadi, Dika Ruslaninur; Hartanto; Wiryadi, Uyan (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
Criminal acts due to the negligence of the perpetrator resulting in traffic accidents and serious injuries and/or deaths according to Law Number 22 of 2009 concerning Traffic and Road Transportation are regulated in Article 229 paragraph (1) of Law Number 22 of 2009 concerning Traffic and Road Transportation, although Article 229 paragraph (1) letter c of the Law on Traffic and Road Transportation has regulated the rights of victims regarding compensation for losses from victims, however, the compensation for losses is only limited to medical expenses and/or funeral expenses and compensation for losses the amount of which is determined by a court decision, which means that the compensation for losses may not necessarily be able to restore the losses suffered by the victim's family. By remembering and paying attention to Article 310 paragraph 3 of Law Number 22 of 2009 and Article 193 of the Criminal Procedure Code, it is correct. Implementation of the Panel of Judges' Decision on Criminal Acts of Negligence Causing Traffic Accidents and Resulting in Serious Injuries and Death of Others in Decision Number 212 / Pid.Sus / 2023 / PN Idm. and Decision Number 238 / Pid.Sus / 2024 / PN. In fact, the defendant's negligence has caused the loss of 2 lives, in addition, the defendant's negligence has caused 2 victims to suffer minor injuries and one person to suffer serious injuries. The Panel of Judges considered that the defendant had been responsible by replacing all losses suffered by the victim and assisting in the evacuation process of the victim. In fact, Article 235 paragraph (1) of Law Number 22 of 2009 concerning Traffic and Road Transportation explains that in the case of a driver who has caused death and has provided assistance to the victim's heirs in the form of medical expenses and / or funeral expenses, it will not dismiss the criminal case charges.